On pathological solutions to an optimal boundary control problem for linear parabolic equation with continuous coefficients - Gorbonos, S.O.; Kogut, P.I. (Кибернетика и вычислительная техника, 2014)
Изучена задача оптимального управления для линейного параболического уравнения с неограниченными коэффициентами в главной части эллиптического оператора. Особенностью данного уравнения является то, что матрица потока является кососимметрической, а ее коэффициенты принадлежат к пространству L² . Показано, что поставленная задача имеет единственное решение, которое нельзя получить, используя L∞ аппроксимированных задач. Досліджено задачу оптимального керування для лінійного параболічного рівняння з необмеженими коефіцієнтами в головній частині еліптичного оператора. Особливість даного рівняння полягає в тому, що матриця потоку є кососиметричною, а її коефіцієнти належать до простору L² . Показано, що поставлена задача керування має єдиний розв’язок, який не можна досягти через границю оптимальних розв’язків для L∞ апроксимованих задач. The purpose of this work is to give the example of an optimal control problem for parabolic equation with unbounded coefficients such that its unique solution has special singular properties. We show that because of these properties, a numerical simulation for a given class of optimal control problems is getting nontrivial. Results: We prove that under special choice of the matrix of coefficients in an elliptic operator and the special construction of the right-hand side of the linear parabolic equation, a unique solution to the original optimal control problem has a singular character and it cannot be attainable through the solutions of the similar optimal control problems with bounded coefficients.